Faktor Yang Berhubungan dengan Perilaku Personal Hygiene Saat Menstruasi pada Santriwati di MTs Pondok Pesantren Dar El Hikmah Kota Pekanbaru - Maharani, Riri; Andryani, Weni (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
Someone is said to have a personal Hygiene well if that person can keep their body hygiene including skin, teeth, and mouth hygiene, nose hair, ears, legs and nails seta genetalia equipment, one of genitalia tool maintenance can be done on young women during menstruation. Based on the initial survey at MTs Darul Hikmah Pekanbaru from 15 menstruating santriwati, 10 of them did not know about personal hygiene during menstruation, due to not hygiene during menstruation, they tend not to behave hygiene. This study aims to determine the behavior of personal hygiene during menstruation at santriwati in MTs Pondok Pasentren Dar EL Hikmah Pekanbaru City. This research method is quantitative research by using cross sectional. The sample of this research is 148 santriwati class VII and VIII in MTs Darul Hikmah Pekanbaru City. The sampling technique is propability sampling. The analysis used is univariate and bivariate analysis with chi-square test, measuring instrument used is questionnaire and data processing using computerization The result showed that there was a relationship between knowledge (Pvalue = 0,002 with POR = 4,043), attitude (Pvalue = 0,000 with POR = 5,659), source of information (Pvalue = 0,000 with POR = 5,826), role of health worker (Pvalue = 0.001 with POR = 4,451), the role of teacher (Pvalue = 0.001 with POR = 4,200), culture (Pvalue = 0.002 with POR = 3.893) with personal hygiene during menstruation. It is advisable to develop cooperation with related health agencies that enable Dar EL Hikmah Pasentren Pondok to provide healthcare professionals who are competent in the health field. Keywords:Personal hygiene, menstruation, santriwati